2020
DOI: 10.5114/pjr.2020.97955
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plantar fascia using high-resolution ultrasonography in clinically diagnosed cases of plantar fasciitis

Abstract: The aim of this study was to assess the efficacy of high-resolution ultrasonography in the assessment of plantar fascia in individuals with heel pain, before and after treatment. Material and methods: This study was conducted from 2016 to 2019, during which time 44 clinically diagnosed patients of plantar fasciitis were compared to 50 normal volunteers. There were 25 males and 25 females in the control group and 42 females and two males in the study group. Thirty-eight patients had unilateral disease, and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
2
22
1
Order By: Relevance
“…A previous study in the Korean population suggested that a thickness of greater than 3.8 mm was a clinically meaningful US finding of plantar fasciitis [ 8 ]. In the present study, the thickness of the plantar fascia in patients with plantar fasciitis was significantly thicker than in normal controls, but the mean thickness of the plantar fascia in patients with plantar fasciitis ( n = 109 feet) was 3.74 mm, which appears to be less thick than previously reported cases with a mean maximal thickness of 2.9 to 6.9 mm [ 6 , 7 , 33 , 34 , 35 ]. Our finding that the thickness of the plantar fascia in patients with plantar fasciitis was less than that in prior research can be attributed to the following causes.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…A previous study in the Korean population suggested that a thickness of greater than 3.8 mm was a clinically meaningful US finding of plantar fasciitis [ 8 ]. In the present study, the thickness of the plantar fascia in patients with plantar fasciitis was significantly thicker than in normal controls, but the mean thickness of the plantar fascia in patients with plantar fasciitis ( n = 109 feet) was 3.74 mm, which appears to be less thick than previously reported cases with a mean maximal thickness of 2.9 to 6.9 mm [ 6 , 7 , 33 , 34 , 35 ]. Our finding that the thickness of the plantar fascia in patients with plantar fasciitis was less than that in prior research can be attributed to the following causes.…”
Section: Discussioncontrasting
confidence: 82%
“…Second, in cases of plantar fasciitis as well, US findings, such as the thickness of the plantar fascia, did not always correlate with clinical status and vice versa. Previous studies have reported high sensitivity and specificity values of US based on a cutoff value of 4 mm for the diagnosis of plantar fasciitis [ 6 , 7 ]; however, there have also been contrasting results that only 42.7% to 60% of patients with plantar fasciitis exhibited thickening of the plantar fascia to more than 4 mm on US and some research suggests the mean plantar fascia thickness is 2.9 mm in cases of plantar fasciitis [ 35 , 36 , 37 ]. Our results demonstrated that a cutoff value of 3.8 mm for the plantar fascia thickness yielded a sensitivity of 48.6% and specificity of 90.6% with less accurate diagnostic value (AUC 0.63).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three unblinded ultrasound studies reported the number of participants with plantar fascia thickness > 4 mm [ 19 , 22 , 35 ]. Meta-analysis was conducted and included a total of 99 PHP participants and 160 control participants.…”
Section: Resultsmentioning
confidence: 99%